Laugh with Max Linder: Seven Years Bad Luck - Israel, Robert (image Entertainment, 2003)
In Hollywood, Max Linder wrote, produced, and directed and starred in "Seven Years Bad Luck", seen on this DVD complete for the first time since its 1921 released and digitally mastered from an original 35mm tinted print. The hilarious misadventures begin when Max's butler, chasing a maid, breaks an expensive full-length mirror. The butler persuades the cook, who somewhat resembles Max, to stand behind teh frame and be Max's reflection. This gag, developed by Max, has become a classic of film and even television-borrowed by everyone from the Marx Brothers to Abbott and Costello to Red Skelton. In another brilliant sequence, Max flees from the police into a lion's cage, where he proceeds to make friends with the hungry beast. It's the clear inspiration for Charlie Chaplin's very similar scene in "The Circus". "Seven Years Bad Luck" is accompanied by a new small-orchestra score compiled by Robert Israel using authentic period arrangements of silent film music. [www.dvdempire.com]
Keywords: DVD-Video